Design of Automated Departmental Lecture Timetable System - Emmanuel, Etuh; Friday, Ajodoh Onoja; Omolola, Yusuf Serah (Review of Computer Engineering Research, 2019)
A lecture timetable is a tabular list showing the times which a particular lecture is scheduled to hold and the venue in each day of the week. Its content includes the course code for each course, the coded lecture venue, and the time for each lecture. A lecture timetable is designed every semester. In this era of technological advancement, virtually every aspect of human enterprise has been automated (the use of machines especially computers instead of human to accomplish a task). Now students can pay their school fee, register their courses and even check their results on the internet. This is the drive that gave birth to this research work: the design of an automated lecture timetable for the department of mathematical sciences, Kogi State University Anyigba. The project presents the automated design of lecture timetable. The principle of operation is simple and employs the use of computer technology. A program is written in Visual Basic which produces the output in an error free tabular form displaying the courses/venues for each particular lecture schedule.